2006
DOI: 10.4321/s1885-642x2006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Práctica clínica y costes al tratar infecciones por catéter con teicoplanina o vancomicina

Abstract: Objectives: To elicit actual clinical practice of treating intensive care unit patients with catheterrelated infections with teicoplanin or vancomycin from a hospital perspective. As clinical trials have demonstrated similar efficacy of these glycopeptides, a cost-minimisation analysis was also carried out. Methods: The Delphi survey technique was used to gather the opinion of nine physicians regarding resource utilization associated with teicoplanin and vancomycin. Treatment costs considered were costs of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In clinical practice, several studies have demonstrated that teicoplanin and vancomycin have comparable effectiveness in the treatment of gram-positive infections. [46][47][48][49] Although teicoplanin has higher acquisition costs, its advantages such as a longer half-time, lower side effects, and lack of requirement for routine serum monitoring besides its superior tolerability give it considerable potential preference. [47][48][49] Sancar et al found that the acquisition costs of vancomycin were significantly lower; however, the administration, monitoring, and complications costs were significantly higher.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In clinical practice, several studies have demonstrated that teicoplanin and vancomycin have comparable effectiveness in the treatment of gram-positive infections. [46][47][48][49] Although teicoplanin has higher acquisition costs, its advantages such as a longer half-time, lower side effects, and lack of requirement for routine serum monitoring besides its superior tolerability give it considerable potential preference. [47][48][49] Sancar et al found that the acquisition costs of vancomycin were significantly lower; however, the administration, monitoring, and complications costs were significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] Although teicoplanin has higher acquisition costs, its advantages such as a longer half-time, lower side effects, and lack of requirement for routine serum monitoring besides its superior tolerability give it considerable potential preference. [47][48][49] Sancar et al found that the acquisition costs of vancomycin were significantly lower; however, the administration, monitoring, and complications costs were significantly higher. 48 The authors figured out that the total therapy costs per patient have not differed significantly in comparisons between both medications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations